AB1304 THE RHEUMATOID ARTHRITIS FLARE QUESTIONNAIRE (RA-FQ) IS AN EASY TO ADMINISTER PATIENT-REPORTED OUTCOME MEASURE THAT TRACKS WELL WITH THE CLINICAL DISEASE ACTIVITY INDEX (CDAI) OVER TIME IN PATIENTS WITH EARLY RHEUMATOID ARTHRITIS (ERA) IN 2 DIFFERENT HEALTH SETTINGS. (June 2019) - Bykerk, Vivian; Schieir, Orit; Valois, Marie-France; Hazlewood, Glen; Boire, Gilles; Hitchon, Carol; Bessette, Louis; Thorne, Carter; Keystone, Edward; Tin, Diane; Benson, Caroline; Pope, Janet; et al.
Abstract : Background: RA patients may cancel scheduled visits with their rheumatologist. In clinical practice, a validated patient-reported disease activity measure that tracks well with traditional clinical indices could address an important gap by providing real-time information on RA disease activity when a visit to the rheumatologist is not possible. Objectives: To assess concordance between the 5-item patient-reported Rheumatoid Arthritis Flare Questionnaire (RA-FQ) ( 1, 2 ) and the Clinical Disease Activity Index (CDAI) in patients with early RA (ERA) treated in rheumatology clinics in 2 countries with different health systems. Methods: Data were analyzed from patients enrolled in the Canadian early ArThritis CoHort (CATCH) between Nov 2011 and March 2017 and in the Consortium of early ArThritis Cohorts- USA (CATCH-US) from Dec 2014 to Dec 2018. Both observational studies had a similar design; enrolled patients diagnosed with EIA (< 1 year of persistent symptoms) by a rheumatologist who completed similar regular protocolized clinical assessments, laboratory investigations and PROMs. The RA-FQ, designed to assess worsening of RA Inflammation, is a short composite PROM (total score 0-50) that sums 5 single items (NRS 0-10) querying pain, fatigue, stiffness, function and participation. The present analysis includes patients meeting ACR 1987 or 2010 ACR/EULAR criteria, with RA-FQ and CDAI at baseline and at least 1 other follow up (FU) over 12-months. We compared mean scores of the RA-FQ and CDAI over time and calculated intraclass correlation coefficients (ICC) to assess concordance between measures in the 2 cohorts. Results: The study included 818 Canadian and 75 American early RA patients. Age, male sex, and disease activity was higher in the Canadian cohort, while post-secondary education was higher in the US cohort (Table1 ). RA-FQ and CDAI scores tracked closely with one another over time in both cohorts (Canada ICC: 0.76; US ICC: 0.80) Conclusion: There was high concordance between the RA-FQ and CDAI measures over the 1st year of follow up in 2 early RA samples recruited in 2 countries. The RA-FQ may help patients and clinicians track patient disease activity between clinic visits. References: [1] Bykerk VP et al. RMD Open, 2016 [2] Bartlett SJ et al. J Rheumatol. 2017 Acknowledgement: CATCH: Amgen & pfizer-founding sponsors 2007+; abbvie 2011+; medexus 2013+; eli lilly 2016+, merck canada 2017+, hoffmann-laroche & janssen biotect 2011-2016, ucb & bms 2011-2018, sanofi-genzyme 2016-2017. catch-us: bms, ucb, genentech; cedar hill foundation Disclosure of Interests: Vivian Bykerk Grant/research support from: Mallinckrodt, BMS, Crescendo Biosciences, Sanofi/Regeneron., Consultant for: Amgen, Pfizer, UCB, Scipher, Sanofi/Genzyme/Regeneron, Orit Schieir: None declared, Marie-France Valois: None declared, Glen Hazlewood : None declared, Gilles Boire Grant/research support from: Investigator-initiated studies: Amgen, Abbvie, BMS, Eli Lilly, Merck, Novartis, Pfizer, Consultant for: Advisory boards: Amgen, BMS, Celgene, Eli Lilly, Pfizer, Speakers bureau: Merck, BMS, Pfizer, CArol Hitchon Grant/research support from: Pfizer, UCB (unrelated studies), Louis Bessette Grant/research support from: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Consultant for: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Speakers bureau: Amgen, BMS, Janssen, Roche, UCB, AbbVie, Pfizer, Merck, Celgene, Sanofi, Lilly, Novartis, Carter Thorne Grant/research support from: Investigator-initiated studies: Amgen, Pfizer. RCTs: Abbvie, Celgene, CaREBiodam, Novartis, Pfizer, Consultant for: Advisory board: Abbvie, Amgen, Celgene, Lilly, Medexus/Medac, Merck, Novartis, Pfizer, Sanofi. Consultant: Abbvie, Centocor, Janssen, Lilly, Medexus/Medac, Pfizer, Speakers bureau: Medexus/Medac, Edward Keystone Grant/research support from: AbbVie, Amgen, Bristol-Myers Squibb, F. Hoffmann-La Roche Inc, Gilead, Janssen Inc, Lilly Pharmaceuticals, Pfizer Pharmaceuticals, Sanofi-Aventis, Consultant for: AbbVie, Amgen, AstraZeneca Pharma, Biotest, Bristol-Myers Squibb Company, Celltrion, Crescendo Bioscience, F. Hoffmann-La Roche Inc, Genentech Inc, Gilead, Janssen Inc, Lilly Pharmaceuticals, Merck, Pfizer Pharmaceuticals, Sandoz, UCB., Speakers bureau: Amgen, AbbVie, Bristol-Myers Squibb Canada, F. Hoffmann-La Roche Inc., Janssen Inc., Merck, Pfizer Pharmaceuticals, Sanofi Genzyme, UCB, Diane Tin: None declared, Caroline Benson: None declared, Janet Pope Consultant for: Eli Lilly and Company, Clifton Bingham Grant/research support from: BMS, Consultant for: AbbVie, BMS, Eli Lilly, Genentech/Roche, Janssen, Pfizer, Sanofi/Regeneron, Susan J. Bartlett Consultant for: Pfizer, UCB, Lilly, Novartis, Merck, Jansen, Abbvie